Control of Damping Off Disease Caused by Sclerotium Rolfsii Sacc. using Actinomycetes and Vam Fungi on Soybean in The Dry Land Based on Microorganism Diversity of Rhizosphere Zone - Rochjatun, Ika; Djauhari, Syamsuddin; Saleh, Nasir; Muhibuddin, Anton (AGRIVITA, Journal of Agricultural Science, 2011)
One of the obstacles in the efforts to increase soybean production in Indonesia is disease such as damping off which is caused by Sclerotium rolfsii. In East Java, the intensity of S. Rolfsii reached approximately 8.61% that spread all over Indonesia region, even in our neighbor countries such as Malaysia, Thailand and the Philippines. This research was carried out to determine the efficacy of Actinomycetes and VAM (Vesicular Arbuscular Mycorrhizal) against damping-off attack and the diversity of microorganisms in rhizosfer. Research conducted in the laboratory and screen house on Plant Protection Department, Faculty of Agriculture, University of Brawijaya and in Lawang District Malang. Observation variables include level of pathogen attack and infection rate of dampingoff pathogen. Plant height, number of pods, pod weight, seed weight and weight of 100 seeds from each treatment, diversity and identification of microorganisms in rhizosphere were also observed. The results showed that Actinomycetes and VAM application could decrease the percentage of plant death due to damping-off.  Application of Actinomycetes and VAM gave effect on microorganism diversity of Ratai Rhizosphere but not on Wilis. Keywords: Sclerotium rolfsii, vesicular arbuscular mycorrhizal, actinomycetes, and rhizosphere